Domain growth in alloys - Hawick, Kenneth Arthur (The University of Edinburgh, 1991)
This thesis describes Monte-Carlo computer simulations of binary alloys, with comparisons between small angle neutron scattering (SANS) data, and numerically integrated solutions to the Cahn-Hilliard-Cook (CHC) equation. Elementary theories for droplet growth are also compared with computer simulated data. Monte-Carlo dynamical algorithms are investigated in detail, with special regard for universal dynamical times. The computer simulated systems are Fourier transformed to yield partial structure functions which are compared with SANS data for the binary Iron-Chromium system. A relation between real time and simulation time is found. Cluster statistics are measured in the simulated systems, and compared to droplet formation in the Copper-Cobalt system. Some scattering data for the complex steel PE16 is also discussed. The characterisation of domain size and its growth with time are investigated, and scaling laws fitted to real and simulated data. The simple scaling law of Lifshitz and Slyozov is found to be inadequate, and corrections such as those suggested by Huse, are necessary. Scaling behaviour is studied for the low-concentration nucleation regime and the high-concentration spinodal-decomposition regime. The need for multi-scaling is also considered. The effect of noise and fluctuations in the simulations is considered in the MonteCarlo model, a cellular-automaton (CA) model and in the Cahn-Billiard-Cook equation. The Cook noise term in the CHC equation is found to be important for correct growth scaling properties.
Keywords: Binary systems (Metallurgy); Alloys; Monte Carlo method; Digital computer simulation; Domain structure